An Analysis of Floating Maxim in “It Ends With Us” Movie: Qualitative Research - Wildaniyah, Tazkiyatul; Mu'ammalatun, Astuti; Putri, Siti Novia Ade; Daulay, Irma Khoirot; Toyyibah, Toyyibah (Universitas Muria Kudus, 2025)
An adaptation of Colleen Hoover's novel,